الدوافع الأساسية لمشروع الشرق الأوسط الكبير - محمود, يوسف; الخلف, محمد; فرحة, كمال محمود (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتعرض منطقتنا العربية في الوقت الراهن إلى مشروع غربي خطير تحت ستار الديمقراطية يتناول مختلف النواحي الاجتماعية, والسياسية، والاقتصادية، والثقافية، هو مشروع الشرق الأوسط الكبير. وفي هذا البحث، سوف نلقي الضوء على التطور التاريخي لهذا المشروع حتى وصوله إلى صيغته الحالية والأهداف الحقيقية التي دفعت الدول الغربية, وفي مقدمتها الولايات المتحدة إلى طرح وتبني هذا المشروع، ومن ثم نحاول وضع بعض التصورات لمجموعة من السياسات الكفيلة بمواجهة هذا المشروع، للتقليل قدر الإمكان من الآثار السلبية الناجمة عنه. Our Arab region is currently exposed to a very dangerous western enterprise under the pretext of democracy .This greater Middle East enterprise handles the social, political, economic and cultural ways. In our research we will focus on the historic development of this project and the main targets that lead the Western countries guided by the U.S to expose and adopt this project. We then try to put some conceptions for the policies that can confront this enterprise in order to diminish its negative effects as much is as possible.